Auranofin Releasing Antibacterial and Antibiofilm Polyurethane Intravascular Catheter Coatings - Liu, Hanyang; Shukla, Shashank; Vera-González, Noel; Tharmalingam, Nagendran; Mylonakis, Eleftherios; Fuchs, Beth Burgwyn; Shukla, Anita (Frontiers in Cellular and Infection Microbiology, 2019)
Intravascular catheter related bloodstream infections (CRBSIs) are a leading cause of hospital-acquired infections worldwide, resulting not only in the burden of cost and morbidity for patients but also in the over-consumption of medical resources for hospitals and health care organizations. In this study, a novel auranofin releasing antibacterial and antibiofilm polyurethane (PU) catheter coating was developed and investigated for future use in preventing CRBSIs. Auranofin is an antirheumatic drug with recently identified antimicrobial properties. The drug carrier, PU, acts as a barrier surrounding the antibacterial agent, auranofin, to extend the drug release profile and improve its long-term antibacterial and antibiofilm efficacy and potentially the length of catheter implantation within a patient. The PU+auranofin coatings developed here were found to be highly stretchable (exhibiting 500% percent elongation), which is important for the compliance of the material on a flexible catheter. PU+auranofin coated catheters were able to inhibit the growth of methicillin-resistant Staphylococcus aureus (MRSA) for 8 to 26 days depending on the specific drug concentration utilized during the dip coating process. The PU+auranofin coated catheters were also able to completely inhibit MRSA biofilm formation in vitro, an effect that was not observed with auranofin or PU alone. Lastly, these coatings were found to be hemocompatible with human erythrocytes and maintain liver cell viability.